Role of Cross-training in Orthopaedic Injuries and Healthcare Burden in Masters Swimmers - Baker, Brett D.; Lapierre, Stephanie S.; Tanaka, Hirofumi (International Journal of Sports Medicine, 2019)
We determined whether the incidence of injuries would increase with advancing age and whether the participation in cross-training would be related to a decreased rate of injuries and healthcare costs in Masters swimmers. A total of 499 swimmers (55±14 years of age) belonging to US Masters Swimming completed a comprehensive questionnaire that included questions regarding their medical history as well as their training history. In average, swimmers had been training for 13±12 years, and 35, 40, and 47% participated in running, cycling, and dryland resistance training, respectively. According to the logistic regression, prevalence of injuries increased significantly but modestly with advancing age (p<0.05). Linear regression analysis showed that for every 1 month increase in the length of injury, healthcare costs increased by 7.4% (p<0.05). Linear regression and logistic regression analyses determined that overall volume of swimming training was not related to age or incidence of injuries, respectively. Multinomial logistic regression analyses using age and sex as predictors demonstrated that the odds of reporting a swim-related injury were significantly lower for individuals who participated in any number of cross-training activities compared with those who do not cross-train (p<0.05). Regular participation in any cross-training modality was inversely related to age (p<0.05). We concluded that the diversification of the overall training program by incorporating cross-training may be an important strategy to reduce sport-specific injuries among Masters athletes.
Keywords: non-specific training activities; aging; specificity of training; swimming; healthcare cost